Isolation and molecular cloning of cellulase gene from bacillus licheniformis - Jonnathan, Stephan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Cellulase enzymes have a wide range of applications in various industries. The recent discovery of the complete genome of Bacillus licheniformis has invoked great interest in utilising these bacteria for mass production of the enzyme such as cellulase. Through molecular cloning technology, cellulase derived from the gene of Bacillus licheniformis can be produced at higher rate and quantity by cloning the cellulase gene into Escherichia coli. The enzymatic activity of cellulase produced by Bacillus licheniformis is displayed by using Congo red stained Carboxy Methyl Cellulose agar plate. The cellulase gene from Bacillus licheniformis is isolated by using Polymerase Chain Reaction (PCR) method. The cellulase gene is inserted into a constructed expression vector and the expression of the target protein is optimized through the use of Escherichia coli. Bacillus licheniformis was found to displayed high rate cellulase activity.The findings from this study can serve purpose for future study involving isolation of gene from Bacillus licheniformis.